Social Unionism and Union Power in Public Sector Unions - Ross, Stephanie (Public Sector Unions in the Age of Austerity, 2013)
Analyzes the tendency of public sector unions towards social unionist strategies, including in collective bargaining and mobilizing broader public support for services.
Keywords: Labor Unions; Political activity